Examination of the connection between the theoretical framework and practice of workplace integration in the case of American concerns - Kozák, Anita (Acta Agraria Debreceniensis, 2014)
The first part of this essay presents the definition of workplace socialization, workplace orientation, workplace integration and onboarding on the basis of English literature. It also illustrates the human resources and management tasks and responsibilities in the process of onboarding.Considering the literature I set up questions for a half-structured interview completed with American HR managers by the help of skype program. The results pointed out that the professionals refer only a few elements of definitions, and the onboarding term is used for other HR practices (recruiting, selection), too. Furthermore on the basis of the results the onboarding process in well-organized and managed, and also the related human resources and management tasks and responsibilities are correctly appointed within the examined companies.Additionally this examination verified our previous results which showed that there is a strong documentation and controlling in the process of onboarding within American enterprises.